KERENTANAN SISTEM AIR TANAH TERHADAP KONTAMINASI DAN APLIKASI ISOTOP ALAM NITROGEN-15 DAN SULFUR-34 - E. Ristin Pujiindiyati (Jurnal Ilmu dan Budaya, 2018)
The tend of decreasing groundwater quality recently becomes obvious due to increasing population, urbanization, industrialization and uses of chemicals in agricultural region that influences to a decrease in human health. Most studies of groundwater pollution solely concern to contaminant itself applying chemical parameters, while natural isotope tools is rarely applied.However, isotope methods can be utilized as an addition of chemical parameters to get more comprehensive information such as to define a source of among contaminant sources, geochemical reaction and microbial processes occurring in subsurface. The assessments of groundwater susceptibility toward contamination suffered in surface water can also be conducted through isotope approaches. It is necessary when developing, managing, exploiting and protecting these groundwater reservoir. Isotope of 15 N, for example, can distinguish the source of nitrate contamination in groundwater if it comes from manure, soil or NH 4 NO 3 synthetic fertilizers. Denitrification process can also be recognized by combination of 15 N and 18 O isotopes in remaining nitrates. Isotopes of 34 S and 18 O in sulfates dissolved in groundwater can be used for tracing sea water intrusion, terrestrial evaporate dissolution, atmospheric contribution inherited from fossil fuels, leachate infiltration and sediment sulfide mixture.